Testing Market Efficiency: Evidence From the NFL Sports Betting Market. - Gray, Philip K; Gray, Stephen F (Journal of Finance, 1997)
This article examines the efficiency of the National Football League betting market. The standard ordinary least squares regression methodology is replaced by a probit model. This circumvents potential econometric problems, and allows the authors to implement more sophisticated betting strategies where bets are placed only when there is a relatively high probability of success. In-sample tests indicate that probit-based betting strategies generate statistically significant profits. Whereas the profitability of a number of these betting strategies is confirmed by out-of-sample testing, there is some inconsistency among the remaining out-of-sample predictions. The authors' results also suggest that widely documented inefficiencies in this market tend to dissipate over time.